Myrtaceae do legado das águas – Reserva Votorantim, Tapiraí, São Paulo, Brasil - Sant'ana, Gabriela Zominhani (2019)
Myrtaceae in Brazil includes approximately 1030 species, circumscribed in 23 genera, which characterizes it as the 8th family in number of species in the Brazilian flora. It has great ecological importance and is present in several phytogeographical domains, especially in the Atlantic Forest. The Legado das Águas - Reserva Votorantim is located in the municipalities of Tapiraí, Miracatu and Juquiá, next to large areas of environmental conservation, such as the Carlos Botelho State Park, forming a valuable ecological corridor in the Serra de Paranapiacaba. They are regions where the predominant vegetation is Ombrophylous Dense Forest, regions with high biodiversity in the state. The aim of this work is the taxonomic survey of Myrtaceae species occuring in the Legado das Águas - Reserva Votorantim. For that purpose, we carried out collection expeditions in the area as well as visits to the herbaria with expressive collections of plants collected in the area. The 39 species sampled in the area are presented through photographic records, descriptions and identification key, with Myrcia and Eugenia being the most expressive genera, with the highest number of species (17 and 14, respectively). The other genera sampled in the area were: Campomanesia (three species), Myrceugenia (two species) and Plinia (three species). The Myrtaceae species occurring in the Legado das Águas - Reserva Votorantim correspond to about 14% of the species of this family in the Atlantic Forest for the state of São Paulo.